Tics in the theatre: The quiet audience, the relaxed performance, and the neurodivergent spectator - Simpson, H (Johns Hopkins University Press, 2018)
It’s not unusual to hear people complaining about audience etiquette. Benedict Cumberbatch made headlines in 2015 when he asked that fans refrain from filming him in Hamlet at the Barbican Centre; “nothing,” he said, was “less supportive” (“Hamlet” n.p.). Oliver Burkeman penned an entire Guardian editorial on the horrors of noisy fellow spectators, cheerfully recalling an usher “who lectured the noisemakers so forcibly and successfully” that the very memory can still, he confesses, “thrill” him (n.p.). So keen is the modern sense of the need for respectful silence, so quick is the modern spectator to condemn those who contravene established theatre etiquette, that one might quickly forget that the concept of the ‘quiet’ or ‘invisible’ audience is both a recent and a historically atypical one. As a result, it is also easy for the modern spectator to forget how the cult of the ‘quiet’ audience presents a sometimes insurmountable challenge to the neurodivergent spectator, whose cognitive and/or physical functioning may mean that she cannot guarantee that her body will remain quiet during the length of a performance. Alongside what Max Barton calls “audience attitudes that are potentially linked to disrespect, such as heckling, using phones and crackling sweep and crisp packets” (n.p.), much other audience noise that signals only an alternatively functioning body is condemned as equally inappropriate or disrespectful in the theatre auditorium: the verbal tic or motor convulsion of the person with Tourette syndrome, the repetitive tapping of the individual with OCD, or the self-comforting rocking of the child with autism. Partially as a result of such stringent policing of ‘quiet audience’ etiquette, individuals with a disability or long-term illness have significantly lower rates of arts attendance than others (Smith 40). The acceptance of ‘quiet audience’ etiquette as theatrical norm radically decreases the auditorium’s accessibility. However, the neurodivergent spectator’s presence in the auditorium offers a new perspective on theatre’s value as an embodied communal event. This essay begins by tracing how the modern prioritizing of the quiet audience has prevented neurodivergent individuals from accessing theatre spaces. It then uses this grounding to explore how re-establishing the ‘relaxed audience’ as an institutional norm might affect the potential of the theatre auditorium as a public sphere. Rethinking ‘quiet audience’ etiquette not only benefits the neurodivergent spectator who might otherwise struggle to access the mainstream theatre auditorium; it also puts a renewed emphasis on the theatre’s fundamental construction as a live, embodied encounter with other individuals.